Biomarkers of Ossification of the Spinal Ligament. Issue 6 (September 2019) - Kawaguchi, Yoshiharu
Study Design: Literature review. Objectives: To review biomarkers in patients with ossification of the spinal ligament (OSL), including ossification of the posterior longitudinal ligament and ossification of the ligamentum flavum and to raise the present issues. Methods: A literature search was performed using PubMed and MEDLINE databases. The biomarkers were classified according to category. The number of the subjects and reproducibility were assessed. Results: Eleven articles were included in this review. There were 9 articles from Japan, 1 article from Taiwan, and 1 article from China. The biomarkers were classified into calcium-phosphate metabolism markers, bone turnover markers, sclerostin, dickkopf-1, secreted frizzled-related protein-1, fibroblast growth factor-23, fibronectin, menatetrenone, leptin, pentosidine, and hypersensitive C-reactive protein. However, there were several limitations in the research studies, such as small research field, small number of subjects, and a lack of reproducibility. Conclusions: Although there have been several studies that have analyzed biomarkers for OSL, there are no definitive conclusions to date. Numerous issues will need to be resolved in the future. It is imperative to continue this research because the results might prove beneficial to elucidate the pathology of OSL and the measures to prevent the initiation and progression of the disease.